Taurine treatment prevents derangement of the hepatic γ‐glutamyl cycle and methylglyoxal metabolism in a mouse model of classical homocystinuria: regulatory crosstalk between thiol and sulfinic acid metabolism. Issue 3 (3rd January 2018) - Maclean, Kenneth N.; Jiang, Hua; Aivazidis, Stefanos; Kim, Eugene; Shearn, Colin T.; Harris, Peter S.; Petersen, Dennis R.; Allen, Robert H.; Stabler, Sally P.; Roede, James R.
Abstract : Cystathionine β‐synthase‐deficient homocystinuria (HCU) is a poorly understood, life‐threatening inborn error of sulfur metabolism. Analysis of hepatic glutathione (GSH) metabolism in a mouse model of HCU demonstrated significant depletion of cysteine, GSH, and GSH disulfide independent of the block in trans‐ sulfuration compared with wild‐type controls. HCU induced the expression of the catalytic and regulatory subunits of γ‐glutamyl ligase, GSH synthase (GS), γ‐glutamyl transpeptidase 1, 5‐oxoprolinase (OPLAH), and the GSH‐ dependent methylglyoxal detoxification enzyme, glyoxalase‐1. Multiple components of the transcription factor nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2)‐mediated antioxidant‐response regulatory axis were induced without any detectable activation of Nrf2. Metabolomic analysis revealed the accumulation of multiple γ‐glutamyl amino acids and that plasma ophthalmate levels could serve as a noninvasive marker for hepatic redox stress. Neither cysteine, nor betaine treatment was able to reverse the observed enzyme inductions. Taurine treatment normalized the expression levels of γ‐glutamyl ligase C/M, GS, OPLAH, and glyoxalase‐1, and reversed HCU‐ induced deficits in protein glutathionylation by acting to double GSH levels relative to controls. Collectively, our data indicate that the perturbation of the γ‐glutamyl cycle could contribute to multiple sequelae in HCU and that taurine has significant therapeutic potential for both HCU and other diseases for which GSH depletion is a critical pathogenic factor.—Maclean, K. N., Jiang, H., Aivazidis, S., Kim, E., Shearn, C. T., Harris, P. S., Petersen, D. R., Allen, R. H., Stabler, S. P., Roede, J. R. Taurine treatment prevents derangement of the hepatic γ‐glutamyl cycle and methylglyoxal metabolism in a mouse model of classical homocystinuria: regulatory crosstalk between thiol and sulfinic acid metabolism. FASEB J. 32, 1265‐1280 (2018). www.fasebj.org